Criteria Air Pollutants and their Impact on Environmental Health - Saxena, Pallavi; Sonwani, Saurabh; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
Air pollution is a global hazard. Majority of the world's population is affected by air pollution. Contamination of air is no more an only an atmospheric problem but now has become a health concern too. Under the Clean Air Act of 1971, a set of air pollutants are designated as criteria pollutants. These are suspected to be strongly harming the public health and the environment as compared to other primary and secondary pollutants. Globally, this category of air pollutants has been given less attention, only few studies have been reported in this area. This book begins with a short background on criteria air pollutants and their sources, sinks and chemistry. The chapters explore the detailed nature of primary pollutants criteria pollutants such as nitrogen dioxide, sulphur dioxide, carbon monoxide, particulate matter and lead. Their reaction mechanisms, climate change potency, environmental health effects on plants and human life are discussed. The book also covers secondary pollutants such as ozone. The book discusses ozone chemistry and its environmental health effects. This book act as a valuable tool for students in Environmental Science, Biological Science and Agriculture, as well as environmental consultants and professionals involved in air quality research and the application of air quality guidelines and advice.
Tentative Table of Contents- 1. Introduction -- 2. Criteria Air Pollutants: chemistry, sources and sinks -- 3. Primary Criteria Air Pollutants: Environmental Health Effects -- 4. Secondary Criteria Air Pollutants: Environmental Health Effects -- 5. Policy Regulations and future recommendations.
Keywords: Analytical chemistry; Environmental chemistry; Climatology; Atmospheric science; Analytical Chemistry; Environmental Chemistry; Climate Sciences; Atmospheric Science